The effect of different fields of tertiary education on economic growth - Müzeyyen Merve Serifoglu; Pelin Öge Güney (Review of Economic Analysis (REA), 2022)
The purpose of this paper is to analyze empirically the contribution of tertiary level education by fields on economic growth for 29 developed and 25 developing countries over the period 1998-2012. Using the two-step System Generalized Method of Moments (GMM), we find that in the developed countries graduates from science faculties make the most contribution to economic growth, but in developing countries graduates from education, humanities and social sciences faculties contributed the most to economic growth. In addition, we focus on the effectof distribution of tertiary level graduates among different fields on economic growth and our results imply that, having human capital from different fields in both developed and developing countries positively affects economic growth.
Keywords: I23; J24; O1; 330; tertiary education; graduates by field; distribution; economic growth; system GMM